Bloom of the flower dragon - West, Tracey, 1965- (West, Tracey, 1965- Dragon Masters, 2022)
Drake and the other Dragon Masters help Wildroot, a Flower Dragon whose home is in danger, find his Dragon Master Oskar after Oskar's identity is revealed to them by the Dragon Stone.